EFEKTIVITAS IMPLEMENTASI KEBIJAKAN SISTEM MANAJEMEN MUTU PADA PENDIDIKAN DAN PELATIHAN KEPEMIMPINAN (Studi Kasus Pelaksanaan Diklat Kepemimpinan Tingkat III pada Badan Pendidikan dan Pelatihan Daerah Provinsi Jawa Barat) - Dudung Sumahdumin (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2010)
The West Java Regional Board of Education and Training (Badiklatda) is responsible to improve the quality of continuous operation of its education and training programs. Despite Badiklatda’s policy in adopting ISO 9001:2000 since 2004, it has not shown any significant quality improvement yet in its education and training programs. The objective of this study is to identify, hence to comprehend constraints that may obstruct accelerated quality development of Diklkat’s programs as reflected by the poor learning process and disproportionate transfer of knowledge. The other objective is to create models using the seven criterias of Baldrige National Quality Program. Diklat’s model based on quality target becomes significantly strategic.